PENGARUH ETOS KERJA, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING DI LINGKUP KECAMATAN JETIS - Budiarjo, Mokhammad Satrio; Kasnowo, Kasnowo (BBM (Buletin Bisnis & Manajemen), 2025)
In the era of increasingly advanced globalization, employee performance in a company is important, there are several factors that influence employee performance, namely work ethic. This research aims to determine the influence of work ethic, work discipline and work environment on employee performance with work motivation as an intervening variable in Jetis District. The sampling technique for this research is a non-probability sampling technique, considering respondents who have been appointed as civil servants (Civil Servants) and a sample of 31 was obtained. The data analysis technique uses path analysis using SPSS 27 and quantyspy.org. The research results show that work ethic, work discipline and work environment simultaneously influence employee performance, work ethic influences employee performance with work motivation as an intervening variable, work discipline has no effect on employee performance with work motivation as an intervening variable and the Sobel test of The indirect influence of the work environment has no effect on employee performance with work motivation as an intervening variable in Jetis District.